Teknologi Smart Digester untuk Mengembangkan Budaya Mandiri Energi Bagi Warga Desa Banjarsari Kabupaten Madiun - Nurmalasari, Riana; Siswanto, Ely; Sunaryo, Nonny Aji; P. P. S, Gladis Viona (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
One of the areas in Madiun where the majority of the population has livestock is Banjarsari Village. Unfortunately, the large number of residents who have livestock has not adequately balanced with managing or processing animal waste. If managed and processed correctly, livestock waste has benefits and can produce economic value. One of the efforts to manage and process sound livestock waste is to utilize it as an energy source, such as biogas. Biogas produced from livestock waste can be used to meet the daily energy needs of the community. To produce good quality biogas, technology is needed to process and process it, namely a digester. Based on the results of livestock waste processing, the digester barrel's capacity is 150 - 200 litres. The capacity of the biogas bag is 500 litres. When complete, the biogas bag can produce gas for 60 to 120 minutes of cooking. This condition allows the community to produce energy independently by utilizing livestock waste for daily needs.